2023
DOI: 10.18006/2023.11(2).290.296
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of protein extraction from "Cam" rice bran by response surface methodology

Le Thi Kim Loan,
Quoc Ha Minh,
Thuy Nguyen Minh
et al.

Abstract: "Cam" rice bran was considered a waste product from rice, which is rich in natural compounds and protein owing to its outstanding nutritional value. This study aimed to establish an optimization model for extracting protein from rice bran, with two responses: extraction yield (%) and protein content (%). The variable parameters included were pH (8.5-9.5), stirring time (3.5-4.5 h), and enzyme incubation temperature (85-95°C). The coefficient of determination for both models were above 0.95, indicating a high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It has traditionally been utilized for culinary purposes and has also served as a primary ingredient in the production of a range of products, including instant rice, germinated rice flour, and gluten-free bread (Le Loan et al, 2021;Le et al, 2022;Le & Nguyen, 2019;Loan et al, 2023c;. Nevertheless, subsequent to undergoing the milling and polishing procedures, the rice bran known as "C ầm" was also discarded, and its utilization was not appropriately executed (Loan et al, 2023a;Loan et al, 2023b). In a recent study conducted by Loan et al (2023a), it was shown that the "C ầm" rice bran possesses significant potential for the development of value-added products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has traditionally been utilized for culinary purposes and has also served as a primary ingredient in the production of a range of products, including instant rice, germinated rice flour, and gluten-free bread (Le Loan et al, 2021;Le et al, 2022;Le & Nguyen, 2019;Loan et al, 2023c;. Nevertheless, subsequent to undergoing the milling and polishing procedures, the rice bran known as "C ầm" was also discarded, and its utilization was not appropriately executed (Loan et al, 2023a;Loan et al, 2023b). In a recent study conducted by Loan et al (2023a), it was shown that the "C ầm" rice bran possesses significant potential for the development of value-added products.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, subsequent to undergoing the milling and polishing procedures, the rice bran known as "C ầm" was also discarded, and its utilization was not appropriately executed (Loan et al, 2023a;Loan et al, 2023b). In a recent study conducted by Loan et al (2023a), it was shown that the "C ầm" rice bran possesses significant potential for the development of value-added products. This is attributed to its high protein content and the presence of other essential elements.…”
Section: Introductionmentioning
confidence: 99%